The impact of INCLUSP on university access - Pereira, Marília Gouvêa de França (2019)
University of São Paulo (USP) implemented its first affirmative action policy (AA) for university access in 2007. However, little is known about the effects on the student body, as well as the efficacy of bonus-based AAs in general. This masters thesis carried out a detailed evaluation of this bonus-based program, INCLUSP, using a differences-indifferences approach. We measured the effect of the program on the probability of eligible applicants entering the university and analyzed the profile of students before and after the AA. Thus, we expect to both contribute to the academic literature and the public policy debate at USP and other selective universities. We find that the admission probability of eligible applicants significantly increased after the implementation of the AA and that the policy also seems to be redistributive regarding socio-economic characteristics of the admitted students.